Digital Life Insurance- A Post Covid Agenda - Bedi, Ridhima (Gyan Management Journal, 2023)
Covid19 outbreak has not spared any sector. The entire Service sector was majorly impacted by this deadly virus. But Life Insurance was one of the sectors which benefited in this period. Digital services are the need of the time. Technology has become the backbone of every service industry and Insurance enhanced their services in the post covid era. Though the Insurance Industry was one of the quickest to adopt technology in the services but left itself behind with its updating. Insurance provides not just security but also encourages savings and provides long term funds with overall economic growth. This paper focuses on the extensive literature review of digital trends in the life insurance sectors and the hinderance faced by the life Insurance sector in digital adoption post covid. The results of the study showed the need of digital insurance in the rural areas as well as its importance in the untapped areas as Insurance penetration is not at its peak yet despite of all the years in this business. The study also shows various hurdles faced by the life insurance industry in the digital adoption with various suggestions to coop-up with the current tech era.